Proposals for university promoting in QS rating based on the methods of statistical analysis - A. A. Mikryukov; M. S. Gasparian; D. S. Karpov (Статистика и экономика)
The purpose of the study. The purpose of the study is to develop scientifically based proposals to increase the university performance indicators in the international institutional rating QS to the required values, taking into account the presence of a combination of latent (hidden) factors, the degree of achievement of the set values of the basic indicators and, as a result, the university ranking level.Materials and methods. To achieve this goal, methods of statistical analysis (correlation-regression and factor analysis) were used, which made it possible to identify the degree of influence of latent factors on basic indicators and the main indicator (rating functional). During the study, the following tasks were solved: identification of latent factors affecting the basic indicators of the university, an assessment of their significance and degree of influence on the basic indicators, as well as their grouping. Based on the results of the correlation - regression and factor analysis, measures are formulated to achieve the specified values of the QS University institutional rating indicators.Results. An approach to solving the problem of providing conditions for achieving the required values of university performance indicators in the international institutional ranking QS using models developed based on the methods of correlation-regression and factor analysis is proposed. Estimates of the relationship of indicators and university ranking based on the methods of correlation and regression analysis are obtained. A comparative analysis of the results obtained at the universities of the reference group is made. The problem of identifying factors that influence the change in the values of indicators is solved; the degree of this influence is assessed. Based on the results obtained, reasonable proposals have been developed to achieve the required values of the basic indicators and the rating functional of the university.Conclusion. The results obtained in the course of the study made it possible to justify the measures necessary to solve the problem of achieving the specified performance indicators of the university. Based on the correlation model, correlation dependencies between the rating functional and basic indicators are obtained. Interpretation of the results of factor analysis allowed us to identify a set of factors that have a significant impact on the basic indicators. It is shown that measures to achieve the specified indicators must be carried out taking into account the revealed correlation dependencies between factors and basic indicators, as well as the interpretation results of the developed factor model.